Combining transcranial direct current stimulation and robotic-assisted training to address upper extremity deficits in acute disseminated encephalomyelitis: a case report - Maureen Ahiatsi; Matthieu Vincenot; Christian Bocti; Guillaume Léonard; Marie-Hélène Milot (Journal of Rehabilitation Medicine - Clinical Communications)
A 45-year-old woman with persistent acute disseminated encephalomyelitis sequelae participated in a 4-week robotic-assisted training program of her affected arm combined with transcranial direct current stimulation. Clinical indicators such as range of motion, motor function of the affected arm, fatigue, pain, spasticity, and quality of life were assessed pre/post-intervention. The results demonstrated clinical benefits post- intervention, with an improvement in range of motion and affected arm motor function, fatigue, and quality of life of the patient. Although preliminary, the results of this case report support the development of innovative technologically assisted rehabilitative strategies for individuals with acute disseminated encephalomyelitis sequelae, including a robot-assisted rehabilitation program coupled with neurostimulation sessions. Further large-scale randomized controlled trials are needed to confirm these findings and rigorously assess the efficacy of this approach in acute disseminated encephalomyelitis individuals.